Propuesta de un programa de manejo de residuos sólidos domiciliarios generados en la parroquia rural El Tambo, Cantón Catamayo - Cango Capa, Sebastián Andrés (2023)
The inadequate management of solid waste constitutes a major problem worldwide, in addition to causing social, economic and, above all, high environmental costs for the world's population. The rapid increase in population, changes in consumption patterns and the reduction in the useful life cycle of products have contributed to the increase in the production of solid waste, contributing to the depletion of natural resources. Therefore, the objective of this study is to propose a management program for household solid waste generated in the rural parish of El Tambo. Within the methodological part, a characterization of solid waste was carried out that allowed per capita generation, physical composition and density to be obtained, a diagnosis was also carried out in order to determine the current problem through surveys, interviews and direct observation. The main results obtained during the sampling determined that the per capita generation is 0.34 kg/hab/day, the physical composition included 60.18 % organic matter and 39.82 % inorganic waste and a density of 103.83 kg/m3, some problems were also identified such as: low environmental education, inadequate disposal of solid waste, lack of municipal policies in the parish and the lack of utilization projects. According to the data obtained, a household solid waste management program was proposed taking into account three fundamental aspects such as environmental education; the classification and storage of solid waste; and the use of organic and inorganic waste, thus contributing to improving the quality of life of the population and mitigating environmental pollution.